Identification of BRCA1 Exon15 Mutations in Bangladeshi Ovarian Cancer Patients - Sharmeen, Samina; Bashar, Farhana; Islam, Rumana; Sultana, Mahbuba; Begum, Kamrun Nahar (Mugda Medical College Journal, 2025)
After cervical and uterine cancer, ovarian cancer is the third most frequent gynecological malignancy worldwide. BRCA1 mutations are the common predisposing factors for ovarian cancer development. Among the South Asian countries, most of studies are focused on Chinese, Indian, Pakistani populations. This study aims to identify BRCA1 exon15 mutations in a Bangladeshi ovarian cancer and benign gynecological disease patient population. This cross-sectional, comparative study was carried out in the Genetic Research Laboratory, Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from March 2020 to July 2021. The mean age at diagnosis of ovarian cancer patients was found 44.9 years and benign gynecological diseases patients was found 35.6 years. Among them, about 40% patients were multiparous and 26.7% had family history of cancer. Upon Sanger sequencing of the targeted region (BRCA1 exon15) of the extracted DNA of thirty (30) ovarian cancer and fifteen (15) benign gynecological diseases patients, a mutation in one ovarian cancer patient was identified. The one mutation in ovarian cancer patient, C.4684C>T (P.Pro1562Ser) where ‘C’ was substituted by ‘T’. This mutation was missense, and it was previously reported in ClinGen Allele Registry. Only 3.33% patient, within the age group of 18-50 years, were found to have mutations in their blood. Among this small samples size, one mutation in blood samples of ovarian cancer patients were identified. Mugda Med Coll J. 2024; 7(2): 82-88